Evaluation of dermoscopy in the diagnosis of naturally occurring dermatophytosis in cats. Issue 4 (16th June 2016) - Dong, Charli; Angus, John; Scarampella, Fabia; Neradilek, Moni
Abstract : Background: A rapid, accurate screening test for dermatophytosis in cats is desirable in clinical and shelter medicine. In human dermatology, dermoscopy is used to identify dermatophyte‐infected hairs by their characteristic comma hair appearance. Similar "comma‐like" hairs have been observed in infected cats. Hypothesis/Objectives: The purpose of this study was to evaluate the usefulness of dermoscopy for the diagnosis of naturally occurring dermatophytosis compared to fungal culture. Animals: A total of 67 cats were enrolled. Methods: This was a descriptive field study. All cats were evaluated by dermoscopy and fungal culture. Dermoscopy was performed with a hand held nonpolarized light dermoscope. Results: Three dermatophyte pathogens were isolated via fungal cultures in 36 cats: Microsporum canis ( n = 31), Microsporum gypseum ( n = 3) and Trichophyton mentagrophytes ( n = 2). Dermoscopy was positive in 21 of 36 cats with culture‐confirmed dermatophytosis. Conclusions and clinical importance: Dermoscopy may be a useful point‐of care‐test to identify infected hairs to sample for dermatophyte cultures, but a definitive diagnosis for dermatophytosis should be based on clinical signs and the results of multiple diagnostic tests. Abstract : Background – A rapid, accurate screening test for dermatophytosis in cats is desirable in clinical and shelter medicine. In human dermatology, dermoscopy is used to identify dermatophyte‐infected hairs by their characteristic comma hair appearance. Similar "comma‐like" hairs have been observed in infected cats.Hypothesis/Objectives – The purpose of this study was to evaluate the usefulness of dermoscopy for the diagnosis of naturally occurring dermatophytosis compared to fungal culture.Conclusions and clinical importance – Dermoscopy may be a useful point‐of care‐test to identify infected hairs to sample for dermatophyte cultures, but a definitive diagnosis for dermatophytosis should be based on clinical signs and the results of multiple diagnostic tests.